Identification of potential pathogenic viruses in patients with acute myocarditis using next‐generation sequencing. Issue 12 (13th August 2018) - Takeuchi, Suguru; Kawada, Jun‐ichi; Okuno, Yusuke; Horiba, Kazuhiro; Suzuki, Takako; Torii, Yuka; Yasuda, Kazushi; Numaguchi, Atsushi; Kato, Taichi; Takahashi, Yoshiyuki; Ito, Yoshinori
Abstract : Myocarditis is an inflammatory disease of the myocardium and leads to cardiac dysfunction and heart failure. Although viral infections are considered to be the most common etiology of myocarditis, the identification of the causative virus is still challenging. Recently, next‐generation sequencing (NGS) has been applied in the diagnosis of infectious diseases. The aim of the current study was to comprehensively analyze potential pathogenic microorganisms using NGS in the sera of patients with myocarditis. Twelve pediatric and five adult patients hospitalized for acute myocarditis were included. Serum samples in the acute phase were obtained and analyzed using NGS to detect pathogen‐derived DNA and RNA. Viral sequence reads were detected in 7 (41%) of the 17 myocarditis patients by NGS. Among these patients, detection of Epstein‐Barr virus, human parvovirus B19, torque teno virus, and respiratory syncytial virus reads by NGS was consistent with polymerase chain reaction or antigen test results in one patient each. A large number of human pegivirus reads were detected from one patient by RNA sequencing; however, its pathogenicity to human is unknown. Conversely, the number of detected virus‐derived reads was small in most cases, and the pathophysiological role of these viruses remains to be clarified. No significant bacterial or fungal reads other than normal bacterial flora was detected. These data indicate that comprehensive detection of virus‐derived DNA and RNA using NGS can be useful for the identification of potential pathogenic viruses in myocarditis. Abstract : We evaluated the utility of NGS to detect potential pathogens of acute myocarditis. Viral sequence reads were obtained in 7 of 17 (41%) cases. A large number of human pegivirus reads was detected from one patient. NGS has the potential to detect the etiologic agent of acute myocarditis.